Letter from Campbell Morfit to James Curtis Booth, August 9, 1880 - Morfit, Campbell (1880)
Campbell Morfit (1820-1897), a distinguished chemist from the United States, co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), thanks Booth for his carte de visite and reminisces. He sends his regrets at their inability to meet face-to-face.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Chemists